Laser-Based Therapy Approaches in the Retina: A Review of Micropulse Laser Therapy for Diabetic Retinopathy - Nagel, Ines; Mueller, Arthur; Freeman, William R.; Kozak, Igor (Klinische Monatsblätter für Augenheilkunde, 2024)
Purpose This review aims to elucidate the mechanisms and clinical utility of subthreshold micropulse laser (SML) therapy in the context of retinal care. Subthreshold or “nondestructive” laser therapy encompasses treatment modalities that induce minimal or no harm to retinal or choroidal tissue and leave no visible sings post-application, while achieving clinical efficacy.Methods A comprehensive review of literature sourced from databases including PubMed, Medline, Embase, Cochrane, and Web of Science was conducted, focusing on articles published before February 2024, and discussing the contemporary use of SML therapy in treating diabetic retinopathy (DR).Results The review presents evidence from scientific literature supporting SML therapy as a viable therapeutic approach for management of DR. Across numerous studies, SML therapy has demonstrated safety and additional therapeutic efficacy without causing damage to underlying retinal tissue.Conclusion Subthreshold laser treatment emerges as a safe strategy for addressing DR. Numerous studies have shown its additional efficacy to anti-VEGF pharmacotherapy, which is the currently approved monotherapy for complications of DR. Ongoing research and clinical investigations aim to further elucidate the mechanisms and optimize the therapeutic advantages of this technology.
Keywords: retina; retinal laser; micropulse laser; diabetic retinopathy